Climate change impact on the energy performance of an air handling unit with two-stage heat recovery - Dimchev Ivan; Terziev Angel; Ivanov Martin; Vassilev Momchil (E3S Web of Conferences)
Climate change affects air handling units with two-stage recovery since these systems are used for heating, ventilation and air-conditioning. Their parameters are affected by changes in each of the seasons. The parameters analysed for each of the three climate zones (colder, average and warmer) are SCOP and annual COP of the entire AHU working in all available modes. Two factors - increase in global temperature and increase in CO2 concentration. Each of these factors has a different impact on seasonal coefficient of performance. The increase in global temperature leads to SCOP decrease by 2.3 to 3.7%. On the other hand, the increase of CO2 concentration in the outdoor air for the last 20 years by 50 ppm or 13.3% leads to an increase in SCOP by 5.5 to 6.9%. For the colder climate annual COP is increased by 2.4% due to climate change but for the other two climates (average and warmer) it is decreased with 1.7 and 3.4%. In the near future a large part of the existing air-conditioning and ventilations systems will not be able to maintain the same indoor air quality as now and this will lead to a deterioration in the quality people’s life.